A Comprehensive Literature Review of Relationship of Inflammatory Bowel Disease and Celiac Disease - Erick Persson Jeffry; Charles Sanjaya Seikka (The International Journal of Medical Science and Health Research, 2025)
Background: The relationship between Inflammatory Bowel Disease (IBD) and Celiac Disease (CeD) has garnered significant attention in recent research, revealing complex interactions that may inform both pathogenesis and treatment strategies. Literature Review: The variability in prevalence rates of CeD among IBD patients, as reported by (Bengi et al., 2019), underscores the complexity of these diseases and the interplay of genetic, environmental, and immunological factors. This is further supported by (Hyun, 2021), who explore the connections between metabolic disorders and IBD, suggesting that chronic intestinal inflammation may predispose individuals to additional health issues, thereby reinforcing the idea of shared inflammatory pathways. Additionally, (Akiyama et al., 2022) elucidates the increased prevalence of CeD in patients with immune-mediated inflammatory diseases, indicating that the coexistence of these conditions can influence clinical outcomes. Finally, (Yemula, 2024) emphasizes the role of gut microbiota in the pathophysiology of CeD, suggesting that microbial changes may influence both conditions. The interconnectedness of IBD and CeD is evident, with shared genetic, immunological, and environmental factors driving the relationship. The literature collectively advocates for further research to clarify these interactions and improve patient management strategies, particularly regarding screening and dietary considerations. Conclusion: In conclusion, the relationship between IBD and CeD is characterized by complex interactions influenced by shared genetic predispositions, environmental factors, and dysregulated gut microbiota. The findings underscore the necessity for a nuanced understanding of these conditions to enhance diagnostic approaches and treatment strategies.